Development of friction stir welding of plastic using vertical milling machine / Faizul Hj Mat Zain. - Mat Zain, Faizul (2009)
Friction stir welding(FSW) process had been used for production welding of aluminium since early 2000AD. Although the performance, quality and application had been described several technical papers presented in international conferences, yet the actual operation parameter of the welding process was treated as industrial secret. The published patent information only described the welding parameter in so wide a range that actually 'hides' the know-how of the welding process and characteristics of the welding machine.